Systematics of the Neopelminae (Aves: Passeriformes: Pipridae) with description of a new genus - Els, Paul Van; Harvey, Michael G.; Capurucho, João M.g.; Brumfield, Robb T.; Whitney, Bret M.; Pacheco, José F. (Zootaxa, 2023)
N/A